Intelligent Fishcarelab System (IFS) for Remote Monitoring of Koi Fish Farming System - Tuhu Agung Rachmanto; Minto Waluyo; Mohamad Irwan Afandi; Basuki Rahmat; Helmy Widyantara; Hariyanto Hariyanto (Future Science)
Intelligent Fishcarelab System (IFS) is designed as online monitoring fish farming system. IFS hardware consists of mechanical and electronic systems. Mechanical system consists of water tanks and piping systems. While the electronic system comprises sensors temperature, pH and Dissolve Oxygen (DO). These sensors include signal conditioning circuit. Furthermore, by using Analog to Digital Converter (ADC) module the data can be read by the microcontroller circuit. Microcontroller circuit is assigned to conduct sensor readings and sends data to the server to inform water conditions. IFS in the operating system hardware requires microcontroller-based software and web-based software for monitoring water quality and feeding automatically and scheduled. Furthermore, this system apart can work directly in the area of fish farming can also be monitored remotely using an Internet connection.